Implementasi Sistem Pendeteksi Asap Kebakaran dengan Mikrokontroler Arduino Dengan Metode Fuzzy Mamdani - Alifah, Nurli; Irawan, Agung Susilo Yuda (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Fire disasters often occur due to various factors, one of which is public negligence and lack of anticipation to prevent fires from occurring. In most cases, the fire is often known when it has grown. Based on these problems, we need a system that can detect fires as quickly as possible from the appearance of smoke to prevent the emergence of a fire that is getting bigger. In this study, the author will create a system in the form of a fire smoke detector using an Arduino Uno microcontroller with the fuzzy mamdan method. The author wants to compare the fuzzy mamdani method and the Arduino device to get the most accurate results possible. Fuzzy reasoning was chosen because this method is able to calculate data that is vague to not vague, commonly called a vague analogy, namely the value used is between 0 and 1. In this system there is an MQ-2 sensor module to detect smoke and an LM35 temperature sensor connected to the Arduino Uno microcontroller. as a center for controlling the work of other devices and a data processing center on the system. And the program is made on Arduino IDE. With an LCD output to display information about the presence of smoke and an output in the form of a buzzer to give a warning sound. In this study, the results showed that the Fire Smoke Detection System Using an Arduino Microcontroller with the Fuzzy Mamdani Method could run well and produce state outputs that were in accordance with the fuzzy calculations in Matlab.